Quality Assurance and Accreditation (QAA) Procedures and Efforts and Students’ Impression in Urlabari Multiple Campus - Karki, Khemraj (New Journey, 2024)
This research paper entitled “Quality Assurance and Accreditation (QAA) Procedures and Efforts and Students’ Impression in Urlabari Multiple Campus” mainly concerns on the procedures and efforts of UMC after the PRT visit form the UGC in Magh, 2080 to get the campus QAA certified and also concerns on the role of the students of UMC to get the campus certified. It equally concerns about the role of students, their knowledge about QAA, functions of QAA, advantages and disadvantages of QAA and other aspects as students are also the part to get the campus certified. This research article is based on mixed method in its nature. The main problem of the study is to find out the procedures and efforts of UMC after the PRT visit and also to find out the students’ perception regarding QAA program. the main objective of the study is also to find out the answer of the problem.to give the paper a complete shape, both the primary and secondary sources of data were collected. 30 students both English and Nepali medium of BBS 1st year were randomly selected and they were provided questionnaire to get the primary sources of data regarding the perception of the students about the QAA program in UMC. Similarly, interview was used as another tool of data collection to find out the procedures and efforts of UMC regarding the achievement of QAA program. The interview was specially concerned with the SAT committee co-ordinator and its members to get the necessary data. The collected data were interpreted by using the tools and techniques of data analysis in mixed method like description, narration, comparison, tables, charts and so on. The research found that among the thirty students 60% were found familiar about the QAA program. 10% students had any idea about the program. 30% students had simple knowledge about QAA program.80% students were found familiar about the program for only a year and 10% were familiar for more than a year and 10% didn’t have any idea about the program. In the same way, only 10% students were found to be familiar about the function of UGC and its program. 83% students agreed that QAA programs are quite beneficial for the campus and students.